The Implementation of Islamic Values Integrated Natural Science Learning in Secondary School - Rohmah, Nur Farida; Sartika, Septi Budi (Science Education and Application Journal, 2023)
This study aims to analyze the implementation of science learning integrated with Islamic values at MTs Bumi Darun Najah. The focus of this research are: 1) learning implementation processing 2) communicative teaching and learning process 3) students' responses 4) learning activities 5) learning outcomes. The subjects in this study were students of 7th grade MTs Bumi Darun Najah. The object of this research is the science teacher. Data collection techniques in this research are observation, interview, and documentation. Data analysis using qualitative descriptive analysis. The results showed an analysis of the implementation of integrated Islamic value learning at MTs Bumi Darun Najah from all aspects of integrating with Islamic values. The aspects include aspects of processing the implementation of learning integrated with Islamic values, communicative teaching and learning processes integrated with Islamic values, learning activities integrated with Islamic values, student responses integrated with Islamic values, and learning outcomes integrated with Islamic values. Suggestions for further research include Islamic value integrated science material and Islamic value integrated teaching materials.